G197(P) Hospital at home for children and young people living in Islington. (27th April 2016) - Hamilton, S; Barnes, J
Abstract : Aims: Hospital at Home (H@H) for Children and Young People living in Islington is an innovative service that aims to: improve patient and family experienc deliver better value care harness the resourcefulness of carers working in partnership with community and hospital providers, and local commissioners Method: Children are referred from the emergency department, ward or community into a'virtual ward'. The child is under the shared care of the acute Paediatric hospital team and the H@H nurses. Care is delivered by a nurse in the home. The child has to be acutely unwell and require: intervention that can be safely given in the community eg IV antibiotics, NGT feeding, nebulisers, oxygen, phototherapy and/or regular monitoring to assess trajectory of illness and/or support to enable carer to look after child at home The service builds on the existing expertise within a nurse led community service by extending the hours and scope of the community nursing team. H@H has overcome three barriers, that often inhibit innovation in health. H@H has created working partnership between: community and acute providers citizens and health care professionals Nurses and healthcare professionals Results: In 15 months, 292 children have received over 53, 000 min of direct patient contact, saving 1470 days in hospital. Qualitative feedback from all sides- parents, young people, paediatricians and commissioners has been postitive indicating improved services for patients and better use of resources. UCLP have conducted a comprehensive ecomonic evaluation of the project. Frontline workers co-designed the IT platform across 4 organisations. Conclusion: 'Integrated working at it's best- well done!' C hildren's Commissioner "It is always scary when your child is not well but the nurses were fantastic. They came to see us every day and I could phone them if I was worried. I was not aware how comprehensive the service would be" Mother There have been many unitended consequences of the services: improved safeguarding and nurses navigating the system on behalf of patients whose condition has deterioriated and escalating concerns on behalf of families. The largest challenge has been for community nurses and actue paediatricians to jointly manage patients in their homes. A new way of working has evolved – one of reciprocal partnership that has allowed H@H to tap into the resourcefullness of the community.